KEBIJAKAN PENGEMBANGAN KARIER DALAM MENINGKATKAN KINERJA - Hadian , Dedi (Majalah Bisnis & IPTEK, 2021)
Organizations that fail to address the problems caused by managerial malaise that afflicts individuals in the organization, also failed to maximize the effectiveness and contribution of the most valuable resources is a talented individual. To create a human being with an organization's human capital needs of intellectual capital, consisting of the capabilities and the ability to use them in work. Career development for employees is certainly an expectation when employees begin and tried to merge into one organization. Stagnation in career development officer would result in low performance of employees. Keywords: human capital; career development